ChemInform Abstract: Mechanistic Understanding of Alkyne Cyclotrimerization on Mononuclear and Dinuclear Scaffolds: [4 + 2] Cycloaddition of the Third Alkyne onto Metallacyclopentadienes and Dimetallacyclopentadienes. Issue 52 (6th December 2016) - Yamamoto, Keishi; Nagae, Haruki; Tsurugi, Hayato; Mashima, Kazushi
Abstract: Review: 108 refs.